Nitrogen and carbon fixation rates and organic matter concentrations from water column samples during RV Maria S. Merian cruise MSM80 off the northern Humboldt Upwelling System - Leila Kittu; Allanah Joy Paul; Mar Fernández-Méndez; Ulf Riebesell (PANGAEA, 2021)
This data is part of the BMBF projects CUSCO (Coastal Upwelling Systems in a Changing Ocean) and BioTip subproject Humboldt Tipping. Here we report water column nitrogen fixation, carbon fixation rates and particulate organic matter composition from the upper 300 m. Data was collected during cruise number MSM80 with research vessel Maria S. Merian from 23.12.2018 - 30.01.2019 (from Panama to Valparaiso) in the Humboldt Upwelling system off the Eastern Tropical south Pacific. Samples were taken by CTD- rosette sampler from different depths, injected with 15N labelled N2 gas based on the modified dissolution method (Großkopf et al., 2012 and Mohr et al., 2010) and additionally 13C labeled sodium bicarbonate. Samples were incubated for 24 hours at light intensities that resemble the in situ light conditions. After incubation a volume of the sample (20 - 1500 ml) was filtered onto a pre-combusted Whatman GF/75 filter. Filters were frozen, transported to the institute on dry ice and measured on a mass spectrometer for Delta15N and 13C (Delta V Advantage Isotope Ratio MS, ThermoFisher) with the ConFlo IV interface (ThermoFisher). Nitrogen fixation rates were calculated based on Montoya et al (1996) while carbon fixation rates were calculated based on the equation by Slawyk et al. (1977). Limits of detection (LOD) and minimum quantifiable rates (MQR) for Nitrogen fixation rates were calculated according to the criteria described by White et al. (2020) and standard error propagation methods described in Gradoville et al. (2017) respectively. POP and Biogenic silica concentrations were measured spectrophotometrically following Hansen and Koroleff (1999).